Optimization and management of flare gases through modification of knock-out drum HP flares by 4R approach based on 3E structures - Ali Ahmadzadeh; Alireza Noorpoor; Gholamreza Nabi Bidhendi (Center of Biomass & Renewable Energy, Diponegoro University, 2024)
The goal of this study is the optimization and management of flare gases through the modification of knock-out drum HP flares. The optimization of the K.O.D. is to create a shell around it and inject water steam into the shell, so that a uniform temperature distribution has done inside the drum, so freezing does not occur, and liquid that drops inside the burner, does not burn. The result of the simulations showed that in the drainage part of the drum, humidity associated with inlet gas freezes upon entering it after pressure and temperature drop suddenly. In the drainage part of the drum and the entrance of water steam with a temperature of 438 K and relative pressure of 550,000 Pa, the freezing of the coating part of it is eliminated. Finally, the water steam with liquid water caused by the heat transfer between the steam, and the bottoms of the drum is out from its drainage part. In the following, two issues were examined. First, simulating the drum to prove the insufficient power of the electric heater at the entrance of the drum. Second, simulating the drum with its surrounding cover in order to eliminate possible freezing. As the result, this work simulated and optimized the K.O.D. flare system to reduce valuable and toxic gas which burned in the flare system and caused environmental, economic, and social effects. This modelling optimized 8 points to add optimum heat flux and used a water steam jacket to prevent the formation of a freezing zone. The optimum zone around the bottom of K.O.D. steam injected this zone and observed no ice formation occurred in this zone. The steam jacket creates uniform heating by using this design and steam injection to the outer wall of the drum. For many reasons, the implementation of this project will reduce smoke and flare pollution: Inhibition of freezing in the liquid outlet of the K.O.D., the liquid level inside the drum remains constant and prevents the transfer of liquid droplets associated with the exhaust gas to the flare.